Spatio‐Temporal Evolution of Earthquake Static Stress Drop Values in the 2016–2017 Central Italy Seismic Sequence. Issue 11 (11th November 2021) - Kemna, Kilian B.; Verdecchia, Alessandro; Harrington, Rebecca M.
Abstract: The static stress drop of an earthquake is an indicator of the stress state of a specific fault before rupture initiation. The stress state is primarily controlled by the ambient stress field, fault strength, fault complexity, and the presence of fluids. This study aims to investigate the spatio‐temporal distribution of static stress drop values of the 2016–2017 multi‐fault rupture seismic sequence in central Italy, which includes three earthquakes with M w ≥ 5.9 (Amatrice, Visso, and Norcia earthquakes), and over 95, 000 aftershocks ( M 0.5–6.5). We estimate stress drop values using a circular crack model with corner frequency and seismic moment estimates from single‐spectra fitting, a cluster‐event method, and spectral‐ratio fitting. The temporal distribution of stress drop values shows an apparent increase of stress drop following a large earthquake ( M w ≥ 5.9). The spatial distribution shows comparably high stress drop values for early aftershocks surrounding the mainshock rupture area. High stress drop events correlate with fault complexity, such as fault intersections at depth and reactivated thrust fronts. We observe a constant stress drop for M w ≥ ∼3, in contrast to previous studies. Instrument response and signal‐to‐noise bandwidth limitations likely govern the observed decrease in stress drop with decreasing magnitude for events with M w ≤ 3. The spatio‐temporal distribution of stress drop values in a complex seismic sequence could support a more complete understanding of the earthquake rupture process and the evolution of seismic sequences. It could also highlight areas where stress loading is focused, which would have implications for short and intermediate term seismic hazard estimates. Plain Language Summary: The ongoing earthquake sequence that began in 2016 in central Italy has produced a significant physical imprint on the earth's surface from the rupture of the three largest events, and has changed the state of stress within the crust. The earthquakes release stored stress in some regions, which can be measured indirectly by the waveforms recorded on seismometers (seismograms), and increase stress in others. Here we analyze seismograms, including those of numerous small earthquakes, to estimate source properties such as the physical size of the rupture surface and the corresponding fault slip. Source properties relate to the amount of stress released by an earthquake and are relevant to learning about the fault rupture process and the redistribution of stress during the evolution of a seismic sequence. We use a combination of approaches to find that the occurrence of large earthquakes leads to a temporal increase of stress in the vicinity of the ruptured fault, and that high stress release correlates with places where faults intersect in the subsurface. Our findings provide a more comprehensive picture of the complex seismic sequence and highlight areas that could influence short and intermediate term seismic hazard estimates. Key Points: The AVN seismic sequence shows significant spatio‐temporal variations in stress drop values Higher stress drop values correlate with increasing fault complexity and stress field heterogeneity Instrument response and signal‐to‐noise limitations likely govern stress drop scaling for events with for M < ∼3